Dietary correlates of temporomandibular joint morphology in the great apes. Issue 2 (7th December 2012) - Terhune, Claire E.
Abstract Behavioral observations of great apes have consistently identified differences in feeding behavior among species, and these differences have been linked to variation in masticatory form. As the point at which the mandible and cranium articulate, the temporomandibular joint (TMJ) is an important component of the masticatory apparatus. Forces are transmitted between the mandible and cranium via the TMJ, and this joint helps govern mandibular range of motion. This study examined the extent to which TMJ form covaries with feeding behavior in the great apes by testing a series of biomechanical hypotheses relating to specific components of joint shape using linear measurements extracted from three‐dimensional coordinate data. Results of these analyses found that taxa differ significantly in TMJ shape, particularly in the mandibular fossa. Chimpanzees have relatively more anteroposteriorly elongated joint surfaces, whereas gorillas tend to have relatively anteroposteriorly compressed joints. Orangutans were most commonly intermediate in form between Pan and Gorilla, perhaps reflecting a trade‐off between jaw gape and load resistance capabilities. Importantly, much of the observed variation among taxa reflects differences in morphologies that facilitate gape over force production. These data therefore continue to emphasize the unclear relationship between mandibular loading and bony morphology, but highlight the need for further data regarding food material properties, jaw gape, and ingestive/food processing behaviors. Am J Phys Anthropol, 2013. © 2012 Wiley Periodicals, Inc.